# Math

posted by .

Find the indicated outputs for f(x)= 5x^2-5x.
F(0) = 0
f(-1)= 1
f(2)= 45

is this right?

• Math -

f(0) = 0 is right
f(-1) = 10
f(-1) = 5(-1)^2 - 5(-1)
= 5(1) - (-5)
= 5 + 5
= 10
f(2) = 10
f(2) = 5(2)^2 - 5(2)
= 5(4) - 10
= 20 - 10
= 10
HOPE THIS HELPS!!

## Similar Questions

1. ### Math

Find the indicated outputs for f(x)=5x^2-2x. f(0)= f(-1)= f(2)=
2. ### Math

Find the indicated outputs for f(x)= 5x^2-2x The 2 after the ^ is an exponent. f(0)=0 f(-1)= f(2)=
3. ### math

can someone check this please find indicated outputs for f(x)= 4x^2 - 2x f(0)=0 f(-1)=6 f(2)=14
4. ### algebra

find the indicated outputs for f(x)=3x^2-5x I get f(0)=0 f(-1) = 1 f(2) =8) am I doing this right if not could you explain where I am wrong.
5. ### math

can someone help me I am not understandng how to do this; Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) <P>indicated outputs 2 <P>F(x) = 4x - 5x
6. ### math

Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated outputs 2 F(x) = 4x - 5x I need help with these can anyone help?
7. ### algebra

find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=
8. ### algebra

Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)
9. ### algebra

Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)
10. ### math

find the indicated outputs for f(x)=3x^2-4x f(0)= f(-1)= f(2)=

More Similar Questions